External Validity of Knee Osteoarthritis Clinical Trials: A Systematic Review - Yun Hyung KOOG; Jin Su LEE Hyungsun WI2 (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the external validity of knee osteoarthritis trials through a systematic review of randomized, placebo controlled, clinical trials. Materials and methods: Randomized trials were identified by searches conducted in PubMed, SCOPUS, and the Cochrane Central Register of Controlled Trials. Then, the number of patients who were screened for eligibility, the number of patients who were eligible, and the number of patients who were randomized in each trial were identified. Results: Overall, 345 reports presenting 352 trials were included in the analysis. Of the trials that reported quantitative recruitment data, the median proportion of screened patients who were eligible for participation was 71.9% (interquartile range: 52.7 to 86.5%) and the median proportion of eligible patients who were randomized in a trial was 92.9% (interquartile range: 82.5 to 100%). The median proportion of screened patients who were randomized in a trial was 67.9% (interquartile range: 48.9 to 92.9%), indicating that three patients were screened for every two patients randomized in trials. When this median value was considered as a reference point, trials conducted for 34% of individual treatments randomized lower proportions of screened patients. Conclusion: Knee osteoarthritis trials were excellently generalizable. However, the generalizability should be considered in relation to all clinical information shown in trials, since a great number of treatments appear to be tested on highly selected patients.